2020
DOI: 10.1111/aogs.13798
|View full text |Cite
|
Sign up to set email alerts
|

The role of levonorgestrel intra‐uterine system in the management of adenomyosis: A systematic review and meta‐analysis of prospective studies

Abstract: Introduction: The levonorgestrel intrauterine system (LNG-IUS) is a long-acting hormone-releasing uterine device that has many non-contraceptive benefits. The study aims to assess the safety and efficacy of LNG-IUS in the management of adenomyosis. Material and methods:We searched the following bibliographic databases: MEDLINE via PubMed, SCOPUS, Web of Science, Cochrane Central Register of Controlled Trials (CENTRAL), EMBASE and Google Scholar for the relevant studies which used LNG-IUS in management of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 37 publications
(46 reference statements)
2
15
0
4
Order By: Relevance
“…The overall effect estimates showed that the use of LNG-IUD leads to significant reduction of pain scores starting at 3 months (standard mean difference [SMD] −1.91, p = 0.002) and persisting at 36 months (SMD −3.81, p < 0.001). Similar trends were noted when assessing heavy menstrual bleeding (SMD −3.58, p < 0.001 at 3 months, SMD −2.32, p < 0.001 at 36 months), and uterine volume (SMD −0.47, p < 0.001 at 6 months, SMD −0.42, p < 0.001 at 36 months) [ 27 ]. Hemoglobin levels were also shown to significantly increase after treatment with the hormonal IUD at 6 months (SMD 1.71, p < 0.001) continuing till 12 months after insertion (SMD 1.6, p = 0.004) [ 27 ].…”
Section: Resltssupporting
confidence: 64%
See 2 more Smart Citations
“…The overall effect estimates showed that the use of LNG-IUD leads to significant reduction of pain scores starting at 3 months (standard mean difference [SMD] −1.91, p = 0.002) and persisting at 36 months (SMD −3.81, p < 0.001). Similar trends were noted when assessing heavy menstrual bleeding (SMD −3.58, p < 0.001 at 3 months, SMD −2.32, p < 0.001 at 36 months), and uterine volume (SMD −0.47, p < 0.001 at 6 months, SMD −0.42, p < 0.001 at 36 months) [ 27 ]. Hemoglobin levels were also shown to significantly increase after treatment with the hormonal IUD at 6 months (SMD 1.71, p < 0.001) continuing till 12 months after insertion (SMD 1.6, p = 0.004) [ 27 ].…”
Section: Resltssupporting
confidence: 64%
“…Similar trends were noted when assessing heavy menstrual bleeding (SMD −3.58, p < 0.001 at 3 months, SMD −2.32, p < 0.001 at 36 months), and uterine volume (SMD −0.47, p < 0.001 at 6 months, SMD −0.42, p < 0.001 at 36 months) [ 27 ]. Hemoglobin levels were also shown to significantly increase after treatment with the hormonal IUD at 6 months (SMD 1.71, p < 0.001) continuing till 12 months after insertion (SMD 1.6, p = 0.004) [ 27 ].…”
Section: Resltssupporting
confidence: 64%
See 1 more Smart Citation
“…GnRH agonists are effective in causing systemic hypoestrogenism to reduce the size of adenomyosis and improve adenomyosis-associated symptoms [ 153 , 154 , 155 ], whereas the side effects of GnRH agonists (menopausal symptoms) limit their use. LNG-IUD has been considered most effective and successfully used to treat adenomyosis because it is efficient in suppressing menstrual bleeding [ 156 , 157 , 158 , 159 , 160 ]. The efficacy of LNG-IUD is generally higher than other progestin-based treatments [ 151 , 152 ].…”
Section: Adenomyosismentioning
confidence: 99%
“…Multiple treatments have been recommended, including hormone therapy, traditional Chinese medicine treatment (CMT), surgery, interventional radiology, minimally invasive therapy and high‐intensity focused ultrasound (HIFU) (Streuli et al., 2014 ; Vannuccini et al., 2018 ; Zeng & Li, 2017 ; Zhou et al., 2011 ). Hysterectomy is the only definitive treatment to cure adenomyosis (Abbas et al., 2020 ); however, it is unacceptable for those young patients who want to keep their fertility.…”
Section: Introductionmentioning
confidence: 99%